LEGAL RESPONSIBILITY FOR UNHYGIENIC PRACTICES AT SEC BOWL RESTAURANT - Anshari, Abu Thalhah Al; Ratrisasi, Elizabeth Prima; Dewani, Maheswari Queena; Januarita, Shintia; Atmadja, Wilhelmina Setia (Awang Long Law Review, 2025)
One of the restaurants that announced the permanent closure of its restaurant branch in Kuningan Jakarta is the Sec Bowl restaurant. The Sec Bowl restaurant is allegedly permanently closed because of a video influencer named Codeblu. Real name William Anderson, he is known as a restaurant and food reviewer who has 14 million followers on TikTok. The content he often uploads is criticism or praise in the form of photos or videos of the food he has tried. Codeblu made a reaction video to a photo sent to him, which showed the condition of the toilet at Sec Bowl. In his video, the influencer said that the place was "very unhygienic" and "very inhumane". Codeblu also suspected that the rice bowl restaurant had violated many ethics and laws. This is certainly very detrimental to consumers. The video has received 62.4 thousand likes and has been shared 15.2 thousand times. The problem is how is the legal regulation of Standard Operating Procedures (SOP) to prevent unhygienic practices in restaurants? What is the legal accountability for unhygienic practices at the Sec Bowl restaurant? The research method used is normative juridical. The results of the study are legal regulations on Standard Operating Procedures (SOP) to prevent unhygienic practices in restaurants that in the case of the Sec Bowl restaurant does not have a Certificate of Hygiene Sanitation (LHS) as per the Regulation of the Minister of Health Number 2 of 2023 page 62 Number 6 point F and legal liability for unhygienic practices at the Sec Bowl restaurant, namely negligence tort liability. In addition, liability for unhygienic practices at the Sec Bowl restaurant can be in the form of compensation if a consumer experiences health problems caused by food from the restaurant.